The Influence of Price, Product Quality, and Service on Apparel Purchase Satisfaction at Emi Boutique - Hasibuan, Nur aida; Lubis, Junita; Syahputra, Rizki (International Journal of Science, Technology & Management, 2022)
The fashion business is a business that continues to grow rapidly, the latest fashions are published every day making business people engaged in this business sector to always keep abreast of the updates that occur. The updates that occur do not only focus on the design and fashion of clothing, but also consumer behavior in the fashion sector, which requires businesses to continue to pay attention to consumer behavior. Consumer satisfaction is the center of attention for companies engaged in the fashion business, not least at Emi Boutique, which is also always crowded with consumers who are looking for the best quality clothes. This research was conducted at Emi Boutique by analyzing the effect of price perception, product quality and service quality on customer satisfaction at Emi Boutique. The study was conducted with a quantitative approach using primary data and analyzed using SPSS. The results of this study indicate that all predictive variables have a specific and significant effect on customer satisfaction who shop for fashion products at Emi Boutique.